THE ESSENCE, FUNCTIONS, AND ROLE OF THE HEALTHCARE SYSTEM IN SOCIETAL DEVELOPMENT - Kasimova D.A; Rustamova D.A; Davlatova Y.Ch (TADQIQOTLAR, 2026)
Annotation: This article examines the essence of the healthcare system, its main functions, and its role in the socio-economic development of society. Healthcare is considered as a key component of social infrastructure that directly influences population health, labor productivity, and overall quality of life. The study analyzes the organizational, economic, and social aspects of healthcare systems, highlighting their importance in ensuring public health protection and sustainable development. Special attention is paid to the interrelation between healthcare effectiveness and national development, as well as the need for continuous reforms and modernization of healthcare services. The findings emphasize that a well-functioning healthcare system is a fundamental factor in strengthening human capital and achieving long-term societal progress.